2012
DOI: 10.4028/www.scientific.net/kem.502.1
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of BPMN 2.0 with other Notations for Manufacturing Processes

Abstract: In order to study their current practices and improve on them, manufacturing firms need to view their processes from several viewpoints at various abstraction levels. Several notations have been developed for this purpose, such as Value Stream Mappings or IDEF models. Recently, the BPMN 2.0 standard from the Object Management Group has been proposed for modeling business processes. A process organizes several activities into a single higher-level entity, which can be reused elsewhere in the organization. Its p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 1 publication
0
6
0
Order By: Relevance
“…In this case, the “non‐interrupting timer” event revels the flow of parallel activities that are triggered when the 30‐days limit for finishing the repair is extrapolated. For this reason, previous research such as those from García‐Domínguez et al (2012) and Erasmus et al (2020) state BPMN is suitable for the detailed process design, and VSM is seen merely as a complement. The hybrid notation proposed in this research, on the other hand, solves the need to work with two distinguished process representation by unifying both notations in a single depiction of the process, preserving their most valued features.…”
Section: Discussion and Practical Recommendationsmentioning
confidence: 99%
“…In this case, the “non‐interrupting timer” event revels the flow of parallel activities that are triggered when the 30‐days limit for finishing the repair is extrapolated. For this reason, previous research such as those from García‐Domínguez et al (2012) and Erasmus et al (2020) state BPMN is suitable for the detailed process design, and VSM is seen merely as a complement. The hybrid notation proposed in this research, on the other hand, solves the need to work with two distinguished process representation by unifying both notations in a single depiction of the process, preserving their most valued features.…”
Section: Discussion and Practical Recommendationsmentioning
confidence: 99%
“…In recent efforts, the widely adopted business process model and notation (BPMN) [41] has seen increasing interest for modeling manufacturing processes. While IDEF, VSM, and UML satisfy most of the requirements mentioned above, BPMN also shows an important advantage with its execution semantics [42]. Moreover, BPMN can be used as a common language for integration of business and manufacturing processes [43,44].…”
Section: Bpmn Modelingmentioning
confidence: 99%
“…However, current manufacturing process management techniques are notoriously rigid [20,21]. In fact, the rigidity of traditional graphical process models has been considered as the main source of process inflexibility [22,23]. Furthermore, the information systems that manage process execution are often blamed for process inflexibility [24,25].…”
Section: Problem Statementmentioning
confidence: 99%
“…Regarding the notation used in this research, BPMN represents a trade-off. Indeed, García-Domínguez et al [23] compared BPMN2.0 with VSM and IDEF3 in terms of the modelling of activity sequences, timing constraints, resource assignment, material flow and information flow. The study found that BPMN2.0 is comparable to IDEF3, with the addition of process participants, event handlers and message flow; however, BPMN2.0 lacks the ability to model the physical aspects of a manufacturing system.…”
mentioning
confidence: 99%